The Cardenolide Glycoside Acovenoside A Interferes with Epidermal Growth Factor Receptor Trafficking in Non-Small Cell Lung Cancer Cells - Hafner, Susanne; Schmiech, Michael; Lang, Sophia Johanna (Frontiers in Pharmacology, 2021)
Cardenolide glycosides are natural compounds known to inhibit the ion pumping function of the Na+/K+-ATPase in cellular systems. Interestingly, various cancer cell types are highly susceptible to cardenolide glycosides. Herein, we explore the cardenolide glycoside Acovenoside A (AcoA) with respect to its influences on human A549 non-small cell lung cancer (NSCLC) cells. We found that exposure to AcoA, digoxin and ouabain increases intracellular sodium and ATP levels indicating that the ion pumping function of the transmembrane Na+/K+-ATPase is effectively inhibited. Like digoxin and ouabain, AcoA inhibits transcription factor NF-κB activation and induces apoptotic cell death in NSCLC cells. This was confirmed by a preclinical in vivo model in which AcoA treatment of NSCLC xenografts grown on chick chorioallantoic membranes inhibited the expression of proliferation antigen Ki-67 and induced apoptotic DNA strand breaks. We aimed to elucidate the underlying mechanisms. The Na+/K+-ATPase transmembrane complex contains Src kinase and epidermal growth factor receptor (EGFR). Indeed, we found that AcoA activates Src kinase in A549 cells, but not in a cell-free assay using recombinant Src kinase. Src kinase is a downstream target of EGFR, and correlation analysis using the NCI60 database pointed to a role of EGFR in cardenolide glycoside-induced cancer cell death. Accordingly, NSCLC cells expressing hyperphosphorylated EGFRmut exhibited resistance to AcoA. To investigate the interaction between cardenolide glycosides and EGFR in detail, we performed immunoblotting studies: Whereas ligand binding and EGFR phosphorylation were not significantly affected, ubiquitinated EGFR accumulated after prolonged incubation with AcoA. To visualize EGFR trafficking we used A549 cells transfected with a fluorescent biosensor which binds to activated EGFR. Pretreatment with AcoA and digoxin induced accumulation of EGFR in endosomal compartments thus inhibiting EGF-induced EGFR degradation comparable to the Na+ ionophore monensin, a known inducer of EGFR endosomal arrest. Intracellular Na+ concentrations regulate EGFR trafficking and signaling. Na+ homeostasis is maintained by the Na+/K+-ATPase, which might account for its close interaction with the EGFR. Cardenolide glycosides inhibit the ATP-dependent Na+/K+ exchange through the Na+/K+-ATPase resulting in higher intracellular Na+ levels. Our data provide first evidence that this impedes efficient EGFR trafficking at the endosomal compartment.